Praktik Jual Beli Thrifthing dan Dampaknya terhadap Pendapatan Pedagang Pasar Pekan 18 Kota Binjai dalam Perspektif Ekonomi Islam - Fiska, Fiska; Waqqosh, Abi; Harahap, Raja Sakti Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to find out how Thrifthing Buying and Selling Practices are and their impact on the Income of Week 18 Market Traders in Binjai City from an Islamic Economic Perspective. The phenomenon of selling Thrift clothing (Used Clothes) not only has a positive impact in reducing textile waste but also has a negative impact on health. This is one of the reasons for the government's ban on importing used clothing. In this study, research was carried out using a qualitative descriptive approach, data was collected through observation and interviews, then analyzed through data reduction and triangulation. The results of the research show that the sale of used clothes at Pekan 18 Market, Binjai City has a big influence on the economic level of traders, the income of traders at Pekan 18 Market, Binjai City is sufficient for the daily needs of traders, the economic situation and also the welfare of the traders are in good condition. From an Islamic Economics perspective, buying and selling transactions at Pekan 18 Market are considered valid because they fulfill the requirements and pillars stipulated in the Muamalah Law. Merchandise such as used clothes can be reused and the substance of the goods is clear and exchange rate (price) conditions are met. However, there is special attention to the cleanliness of merchandise and the process of obtaining it legally, considering the importance of maintaining cleanliness and fairness in transactions.